HUBUNGAN LAMA DAN FREKUENSI PENGGUNAAN GADGET DENGAN PERKEMBANGAN SOSIAL ANAK PRA SEKOLAH DI TK ISLAM AL IRSYAD 01 CILACAP - Sujianti Sujianti (JURNAL KEBIDANAN, 2018)
The use of gadgets among children is increasingly alarming and certainly has a negative impact on growth and development. The ease of accessing various information and technology media causes children to become lazy to move and move. They prefer to sit quietly in front of the gadget and enjoy the world in the gadget. Gradually forget the pleasure of playing with family members. This certainly has a negative impact on children's social development.This study aims to determine the relationship between the duration and frequency of gadget use with the social development of preschool children.The design of this study was descriptive correlative with a cross sectional approach to 53 mothers who had preschool aged children (5-6 years) in Al Irsyad Islamic Kindergarten 01 Cilacap with simple random sampling technique. The type of primary data uses children's social development questionnaire. Data were analyzed by univariate and bivariate with Chi Square test..From 53 respondents, the most normal gadget usage time (60 '/ day) 33 (62.3%), the most normal frequency  44 (83.1%), the best social development 27 (50.9 %).There is no relationship between the duration of using gadgets and the social development of preschoolers.(p:0.577). There is no relationship between frequency of using gadgets and the social development of preschoolers.(p:1.000)